Prévision des précipitations dans la région de Guayaquil - Carlos Lugo (Bulletin de l'Institut français d'études andines, 1998)
An analysis of the mechanisms that induce precipitations in the coastal area of Ecuador and of the relations between precipitation anomalies and temperature and wind anomalies from the Eastern Pacific, allows to determine precipitation monthly forecasting models of the Guayaquil area. Proposed multiple lineal correlation explain 60 to 80% of the February to May precipitation variance using observed data from previous months.